El Buen Retiro y el Conde Duque de Olivares - Chaves Montoya, María Teresa (Anuario del Departamento de Historia y Teoría del Arte, 1992)
The transformation into the magnificent architectural landscape ensemble of the Buen Retiro which was only to be in principle a remodel of the Cuarto Real in San Jerónimo, was due to persistence idea of the Conde Duque de Olivares in creating an appropriate palace for the greatest monarch of that time. The same effort as his royal ancestors had made spending money and efforts in building factories that will always remain joined to their memory. What we are trying to do with the narration of some episodes and new documental informations concerning to the beginning of the palace construction, as for instance the first known description until today published at the very moment of this inauguration, is that to remember supporting or refuting the argumentations that the Conde Duque opposed to the poignant critics against his work, and to emphasize to the protagonisme of the members belonging to the select association of Olivares that in the artistic, financial and administrative aspects made possible its realisation.